Comparison of the Chemical Quality of Sidimpuan Snake Fruit (Salacca sumatrana Becc.) Based on the Color of the Fruit Flesh - Edi Darwan; Rasmita Adelina; Sutan Pulungan; Nuzul Hijri Darlan (PT Inovasi Pratama Internasional, 2026)
This study aims to determine the chemical character of sidimpuan snake fruit, the fruit consisting of vitamin C, total acid, moisture content, tannin content, and dissolved solids (brix) content from three locations, namely Lubuk Raya altitude 700 meters above sea level, Batu Layan is 500 meters above sea level, and Palopat Maria is 463 meters above sea level. The results of the study obtained in white sidimpuan snake fruit were that the vitamin C content of white sidimpuan snake fruit in Lubuk Raya and Batu layan was not significantly different but based on the highest average, the vitamin C content in Lubuk Raya was higher at 41.49% and significantly different from the vitamin C content of white sidimpuan snake fruit in Palopat Maria, which was 28.06 mg/100ml. The total content of dissolved acids was significantly different in Lubuk Raya with a value of 1.68% in Lubuk Raya and the tannin content was significantly different in Lubuk Raya with a value of 0.38 %,. The moisture content of white sidimpuan snake fruit was significantly different with a value of 79.22. % on Palopat Maria. The dissolved solids content of red sidimpuan snake fruit was significantly different with a value of 19.86% in Batu Layan, the observation of vitamin C content, total dissolved acid, water content, and tannin content in red sidimpuan snake fruit from the three locations showed no real difference between salak Lubuk Raya, Batu Layan, and Palopat maria.